2006
DOI: 10.1063/1.2194889
|View full text |Cite
|
Sign up to set email alerts
|

Beam patterns of terahertz quantum cascade lasers with subwavelength cavity dimensions

Abstract: The need to reach single-mode lasing and minimize at the same time the electrical dissipation of cryogenically operated terahertz quantum cascade lasers may result in small and subwavelength cavity dimensions. To assess the influence of such dimensions on the shape of the laser emission, we have measured the beam pattern of two metal-metal cavity quantum cascade lasers. The patterns show regular angular intensity variations which depend on the length of the laser cavity. The physical origin of these features i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
56
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(57 citation statements)
references
References 12 publications
1
56
0
Order By: Relevance
“…It requires low LO power (< 300 nW). This turns out to be crucial for our phase-locking experiment because the QCL has a divergent far-field beam with strong interference patterns [18], resulting in a limited amount of usable power coupled into the mixer. Gunn diode and YIG oscillators).…”
Section: Methodsmentioning
confidence: 99%
“…It requires low LO power (< 300 nW). This turns out to be crucial for our phase-locking experiment because the QCL has a divergent far-field beam with strong interference patterns [18], resulting in a limited amount of usable power coupled into the mixer. Gunn diode and YIG oscillators).…”
Section: Methodsmentioning
confidence: 99%
“…However, for typically used THz QCL waveguides the output aperture is on the order of 10 µm, while the emission wavelength is about 100 µm. This, in fact, leads to a very divergent output beam, which is additionally distorted by interference effects [10,11]. Since external optical elements such as lenses or antennas are difficult to handle on a large scale [12,13], several monolithic concepts have been pursued to address this issue.…”
mentioning
confidence: 99%
“…The spatial structure of wire laser radiation differs drastically from that of conventional lasers with large apertures. It was found to be highly divergent, with strong intensity modulations observed both in far [4] and near field [5], with the pattern of modulations more dense for longer lasers. It was shown that the far-field pattern of wire lasers is formed by the interference of radiation from the longitudinal distribution of sources along the laser waveguide [6] and is similar to that of antennas of traveling wave.…”
mentioning
confidence: 99%